The concept of «home» in the Russian and Chinese language pictures of the world (Eurasian Journal of Philology Science and Education, 2018)
World proverbs large and diverse, and every aspect of his research is certainly worthy of attention. Comparison of the Russian and Chinese proverbs to identify in them similarities and differences in the perception of the world, reflected in the language, is of great interest. We investigate the concept of home» as an important part of the Russian and Chinese culture. Observations received regarding the similarities and differences in the organization of the studied concept, confirmed material of Russian and Chinese proverbs. Specificity of functioning of the concept of «home» in two languages and cultures associated with the common Christian tradition. Identification of the main components of the cultural content of the «home» concept has practical value in teaching Russian as a foreign language on the basis of cultural linguistics.